ILUMINASI NASKAH MELAYU KARYA M. BAKIR KOLEKSI PNRI: TINJAUAN SEMIOTIKA UMBERTO ECO - , CHALIDA NURAULIA AISYANARNI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The objective of this research is to point out types of illumination in Malay manuscripts stored in PNRI, to point out the connection between manuscript illumination and its author or scribe, and to point out the motifs on manuscript illumination using codicology. Furthermore, this research is conducted to identify the significance of motifs in Malay manuscripts illumination written by Muhammad Bakir with regard to the texts and society at the time of making. This significance is analysed using Umberto Ecoâs semiotics. This research also has the objective of pointing out the tradition of manuscript visualisation in the form of types of illumination in Malay manuscript as societyâs creativity in the past. This research applies the theories of philology and semiotics. The theory of philology is used to identify narrative aspects and its illumination. Meanwhile, the theory of semiotics is used to reveal the significance of motifs in Malay manuscript illumination written by Muhammad Bakir with regard to the texts and other contextual things. The result of the analysis shows that there are various styles and motifs in Malay manuscript illumination stored in PNRI. The diversity of motifs in Malay manuscript illumination indicates that Malay society in the past had self-effort approach to the Creator and the universe. The research also shows that most of the illuminated Malay manuscripts stored in PNRI are anonymous. Based on the domination of manuscripts which have complete information about manuscript, the manuscripts illumination written by Muhammad Bakir is used to identify the existence of significance of motifs in the illumination. Based on semiotical analysis, it can be inferred that the motifs in manuscript illumination written by Muhammad Bakir originate from the developing values inside Malay-Betawi society and Muhammad Bakirâs experience as a writer and a person who rented manuscripts. Some of the motifs seen in manuscript illumination written by Muhammad Bakir become the local wisdom for Betawi society until now. In other words, there is continuity between the manuscript in one period and the life of society afterward.